Language use in mass media - "Arokianathan, S." (New Delhi, 1988)
The present study is a significant piece of research that goes into the question of var ability in the use of modern Tamil in mass med a with special reference to radio. The study takes up at length the discussion of Tamil diglossia onto a new plane which will have ramifications for the study of this phenomenon both in other South Asian languages as well as other diglossic languages.
Keywords: Mass-Media and language